Unconscious Transmission in Culture and Education - Morales Barrera, Mónica (2019)
The word transmission is often used in our daily speech as a simple noun, and we find it accompanied by others that give it context, for example, sexually transmitted diseases, television transmission, heat transmission, data transmission, etc.; here it is tangible to distinguish what is transmitted and predict possible outcomes; On the other hand, if we study the particularities of unconscious transmission, we enter loose terrains, as it is an imperceptible phenomenon, whose results can not be controlled. The purpose of this essay is to explore this peculiar mechanism shared by two concatenated areas that are culture and education. This essay addresses examples that we consider paradigmatic to study unconscious transmission, which goes beyond any historical or anthropological proposal. Likewise, conceptual differences are proposed between other apparently similar phenomena such as communication and teaching; we will make special emphasis on the very famous preconceptions about the transmission of knowledge, because since Plato its impossibility is anticipated. Finally, the issue of unconscious transmission in culture and education is linked to that of ethics, as awareness is gained of the power of the unintentional word in the training of learners.